Electronics packaging materials and component-level degradation monitoring - Inamdar, Adwait; Van Driel, Willem D.; Zhang, GuoQi (Frontiers in Electronics, 2025)
Electronic components are complex systems consisting of a combination of different materials, which undergo degenerative changes over time following the second law of thermodynamics. The loss of their quality or functionality is reflected in degraded performance or behaviour of electronic components, which can lead to failures during their operation lifetime. Thus, it is crucial to understand the physics of material degradation and the factors causing it to ensure component reliability. This paper focuses on the physics-of-degradation of packaging materials, which are typically exposed the most to the environmental and operating loads. The content of this article is organised into three parts. First, an overview of the packaging technology and encapsulating materials is presented. Then, the most common degradation-causing factors and package-associated failure modes are reviewed. Lastly, the hardware requirements are discussed, including specialised sensors, measurement techniques, and Digital Twins, to capture the degradation effects and facilitate component-level health monitoring for microelectronics.